Hubungan penerapan atraumatic care oleh perawat dengan stres orangtua selama hospitalisasi bayi - Fivin Maria Ulfa; Eka Oktavianto; Ririn Zuleha (STIKes Surya Global Yogyakarta, 2018)
Hospitalization does not only cause anxiety of the children, but also of the parents. Parental responses to child hospitalization such as: anger, anxiety, insecurity, uncooperative, frustrated and stressful. One of effort to minimize parental stress is the implementation of atraumatic care by nurses. The objective of this study is to know the relationship between the implementation of atraumatic care by nurses with parental stress during the infant’s hospitalization in perinatology ward, Panembahan Senopati Hospital, Bantul, Yogyakarta. The type of this study was non-experimental research, with a cross-sectional design. Purposive sampling Technique was used with total of 95 respondents, whose parents were hospitalized in the Perinatology ward of Panembahan Senopati Hospital, Bantul, Yogyakarta. Data analysis used kendall tau. The results of this study indicated that there was a relationship between the application of atraumatic care by nurses with parental stress during the process of infant’s hospitalization in the Perinatology ward of Panembahan Senopati Hospital, Bantul, Yogyakarta. Kendall tau test results obtained correlation coefficient of 0.889 with p = 0.000 (p value 0.05). The majority of the implementation of atraumatic care was in the good category, that was 43 respondents (45.2%) and the stress experienced by parents in the low stress category, that was 44 respondents (46.3%). The better implementation of atraumatic care, the lower the stress level of parents. The conclusion was There was a relationship between the implementation of atraumatic care by nurses with parental stress during infant’s hospitalization.